The fecal virome of South and Central American children with diarrhea includes small circular DNA viral genomes of unknown origin. - Phan, Tung Gia (2016)
Viral metagenomics of feces collected from 58 Peruvian children with unexplained diarrhea revealed several small circular ssDNA genomes. Two genomes related to sequences previously reported in feces from chimpanzees and other mammals and recently named smacoviruses were characterized and then detected by PCR in 1.7 % (1/58) and 19 % (11/58) of diarrheal samples, respectively. Another three genomes from a distinct small circular ssDNA viral group provisionally called pecoviruses encoded Cap and Rep proteins with <35 % identity to those in related genomes reported in human, seal, porcine and dromedary feces. Pecovirus DNA was detected in 15.5 % (9/58), 5.9 % (3/51) and 3 % (3/100) of fecal samples from unexplained diarrhea in Peru, Nicaragua and Chile, respectively. Feces containing these ssDNA genomes also contained known human enteric viral pathogens. The cellular origins of these circular ssDNA viruses, whether human cells, ingested plants, animals or fungal foods, or residents of the gut microbiome, are currently unknown.